Own emotional awareness - Natsoulas, Thomas (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
A special topic under introspective knowledge is discussed, namely awareness’s of one’s own emotional states. Exposition and interpretation of William James’ theory of emotional consciousness provide one unifying theme. Repeatedly the three major sections return to this theory as they respectively examine basis for subjective emotion in feeling, cognition, and behavior. Tile first section deals with whether emotions, as the subject himself knows and differentiates them, can be adequately characterized as bodily feelings. In the second edition, cognitive aspects of emotion are considered; the cognitive causation of emotion and how the intentionality of subjective emotions might best be understood are explored. In the final section, contributions of behavior to own emotion awareness are discussed, primarily in terms of two theories, in which either (a) feedback from motor attitudes (Bull) or (b) central efferent readiness’s (Arnold) figure importantly in how a subject knowingly experiences his emotions.